2021
DOI: 10.1080/07294360.2021.1945547
|View full text |Cite
|
Sign up to set email alerts
|

Politicising inclusive learning environments: how to foster belonging and challenge ableism?

Abstract: Inclusive learning environments have been described as a crucial factor for fostering disabled students' sense of belonging in higher education. However, few empirical studies have elaborated on how learning environments contribute to disabled students' belonging. In this study, we have taken a socio-political approach and widen the theoretical understanding of 'belonging'. We analyse three Finnish disabled students' narrative interviews concerning their experiences of learning environments through a narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Conceptualising belonging in a time–space context makes the transition from belonging to un-belonging more intelligible. Students may feel closer to the university space at a certain period of their life, attaching themselves to in-person teaching, while in another period, they may feel that the university is not an important setting for them to belong to [ 72 , 73 ]. Some of the text answers emphasised the contextual factors (timing, family or job obligations) to explain their preference for remote teaching.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptualising belonging in a time–space context makes the transition from belonging to un-belonging more intelligible. Students may feel closer to the university space at a certain period of their life, attaching themselves to in-person teaching, while in another period, they may feel that the university is not an important setting for them to belong to [ 72 , 73 ]. Some of the text answers emphasised the contextual factors (timing, family or job obligations) to explain their preference for remote teaching.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the accommodations model can be seen as a way to maintain the status quo of ableism in higher education. Nieminen and Peronen (2021) write, "such approaches have been claimed ableist as they frame disabled students as the problem to be fixed, not the inaccessible design itself" [14]. In our work, we have seen physics instructors rely on this framing to place the blame for struggling in a course on the disabled student.…”
Section: Critiques Of the Accommodations Modelmentioning
confidence: 88%
“…To our knowledge, how students using accommodations are affected by these two-stage collaborative exams is not yet known. Previous research shows that students using accommodations can feel singled out when they perceive their peers are aware that they use accommodations for exams ( Nieminen and Pesonen, 2022 ; Pfeifer et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ; James et al. , 2020 ; Nieminen and Pesonen, 2020 , 2022 ). In an interview study with 37 campus disability resource center (DRC) directors, several aspects of active learning were identified that could negatively influence the experiences of STEM undergraduates with disabilities ( Gin et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation